Reproductive Health Education as Prevention of Unsafe Sexual Behavior among Street Children - Mumun Munawaroh; Syaeful Badar; Abdillah Mushthafa; Kemilau Mutiara Harky; Maghfiroh Maghfiroh; Ade Hidayat (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2026)
This study was driven by the social problems faced by street children related to reproductive health, which contributes to sexual violence, human trafficking, premarital sex, unwanted pregnancies, and HIV/AIDS exposure. This study aimed to provide reproductive health education as a preventive measure against unsafe sexual practices among street children. The research employed a service learning approach, combining survey, observation, interviews, mini workshops, focus group discussions, Q&A sessions, and documentary filmmaking. The findings revealed increased awareness and willingness among street children to access reproductive health services and comprehensive knowledge of reproductive health. The role of peer educators and empathic social support emerged as key factors in program success. This study recommends integrating reproductive health education targeting marginalized groups into relevant university curricula as part of service learning.